The International Competitiveness of the U.S. Textile Mill Products Industry: Corporate Strategies for the Future - Toyne, Brian; Arpan, Jeffrey S.; Barnett, Andy H.; Ricks, David A.; Shimp, Terence A. (Journal of International Business Studies, 1984)
This article reports on the strategic adjustments undertaken by the larger firms of 5 European, 3 Asian Pacific, and the U.S. textile mill products companies during the 1960s and 1970s, and examines several of the underlying reasons for the gradual decline in the U.S. industry's international competitiveness. The study's basic conclusions are that the majority of the foreign textile industries view customer markets differently than the U.S. industry; that they place different emphasis on technology, production, marketing, and strategic planning; and that they have different relationships with their governments than U.S. firms do. The implications of these findings are discussed, and corporate strategy recommendations that are designed to enhance the future international competitiveness of the U.S. industry are presented.